1994
DOI: 10.1083/jcb.127.3.581
|View full text |Cite
|
Sign up to set email alerts
|

Human CENP-A contains a histone H3 related histone fold domain that is required for targeting to the centromere.

Abstract: Abstract. Centromeres are the differentiated chromosomal domains that specify the mitotic behavior of chromosomes. To examine the molecular basis for the specification of eentromeric chromatin, we have cloned a human eDNA that encodes the 17-kD historic-like centromere antigen, CENP-A. Two domains are evident in the 140 aa CENP-A polypeptide: a unique NH2-terminal domain and a 93-amino acid COOH-terminal domain that shares 62% identity with nucleosomal core protein, histone H3. An epitope tagged derivative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
295
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(302 citation statements)
references
References 55 publications
(61 reference statements)
5
295
0
2
Order By: Relevance
“…These results are entirely consistent with basic concepts concerning autoantibodies in systemic autoimmune diseases [15]. Among the three antigens, the cDNA encoding CENP-A was last cloned [16] but a detailed mapping of CENP-A has not been published to date. In a previous study [17], we identified one antigenic epitope of CENP-A at the N-terminal charged region (amino acid sequence 3±17) using ELISA with a synthetic peptide.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results are entirely consistent with basic concepts concerning autoantibodies in systemic autoimmune diseases [15]. Among the three antigens, the cDNA encoding CENP-A was last cloned [16] but a detailed mapping of CENP-A has not been published to date. In a previous study [17], we identified one antigenic epitope of CENP-A at the N-terminal charged region (amino acid sequence 3±17) using ELISA with a synthetic peptide.…”
Section: Introductionsupporting
confidence: 87%
“…It might be due to the usage of the baculovirus system, which can induce modifications in the protein [23,29]. In the N-terminal part of CENP-A, four copies of the peptide Ser/Thr-Pro, which are good candidates for phosphorylation, are present [16]. Some ACA for CENP-A might show a striking preference for conformational epitopes by protein modifications such as phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this unit, we explain in detail how to perform a typical SNAP pulse labeling experiment in human cells. As an example, we will use HeLa cells that stably express a SNAP-tagged version of CENP-A, a centromere specific histone variant (Sullivan et al, 1994;Jansen et al, 2007). Using these CENP-A-SNAP cells, we have been able to show previously that the rate of centromeric CENP-A turnover corresponds to the rate of cell division, and thus that CENP-A turns over exclusively by dilution during DNA replication (Jansen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, CenH3 homotypic nucleosomes associate with centromeric DNA in place of the typical H3s associated with the rest of the genome. The conserved HFD of CenH3 likely performs structural functions similar to the HFDs of other H3s (4) and also is required for targeting CENP-A to the centromere in mammalian cells (37). The precise functions of the divergent N termini are unknown, although it has been suggested that they interact with other centromeric proteins and may play a role in evolutionary suppression of meiotic drive (38).…”
mentioning
confidence: 99%